The Association Between Medication Adherence and Blood Pressure Control in End-Stage Renal Disease Patients with Hemodialysis - Pande Made Desy Ratnasari; Ketut Tia Pran Anggar Yani; Agustina Nila Yuliawati; Anak Agung Ngurah Putra Riana Prasetya (Sanata Dharma University, 2023)
End-Stage Renal Disease (ESRD) is a severe kidney disorder that contributes to an increased risk of mortality in the world. This condition is often related with hypertension. Low medication adherence was affecting uncontrolled blood pressure in ESRD. The research aimed to analyze the association between medication adherence and blood pressure control in ESRD patients. This cross-sectional study with 77 respondents was conducted in September 2020 at the Dialysis Unit of the Private Hospital “X” Buleleng Bali by purposive sampling technique. The respondents must be ≥18 years, diagnosed with ESRD and hypertension, underwent hemodialysis (HD) twice a week, received the same antihypertensive for 3 months, have complete medical record data, and signed the informed consent form. Patients with cognitive impairment, unable to communicate, pregnant or breastfeeding, and received the Erythropoiesis Stimulating Agent (ESA) treatment were excluded. Kruskal-Wallis test was used in data analysis. Most of the patients were 65 years (80.52%), male (70.13%), primary education (57.14%), without complications (57.1%), and duration of illness 5 years (89.61%). Patients were in the high adherence (61.04%) and 66.23% of patients had uncontrolled blood pressure. The association between medication adherence and blood pressure control was not significant (p=0.478). However, these results show that high medication adherence could impact on good blood pressure control.